Indicators of human development in Iraq for the period (2004-2019) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to know the extent to which people are involved in development as both a means and a goal, and what are the achievements made annually within the human development sectors in Iraq, in light of the human development index that is calculated according to the options available to people that are limited to three indicators in terms of application (live a life healthy and long-term, acquiring education and knowledge, and enjoying a decent standard of living, as it gives a relative gradation to countries), and Iraq was classified as one of the countries with medium human development for the period (2004-2019) in light of the challenges facing each indicator.